Why Do the Students Do Disruptive Behavior in English Classroom? A Case Study On Senior High School Students in One of the Small Town in Indonesia - Anida Fadhilah Jati; Endang Fauziati; Agus Wijayanto (International Journal of Language Teaching and Education, 2019)
A conducive learning situation is essential in learning English. However, one problem that usually disturbs the learning situation is the appearance of disruptive behavior. Students' disruptive behavior is an inappropriate behavior conducted by students during the learning process which turns the classroom into unconducive. Exactly, there are several factors contribute to the occurrence of disruptive behavior in the English lesson, especially on senior high school students. Thus, the current study was a case study aimed to investigate several causes of students' disruptive behavior in English teaching-learning process in the classroom. The subjects of this study consisted of an English teacher and a class of twelfth-grade students in a small town in Indonesia. The data were collected using observation and interview. The result of this study showed that students' disruptive behavior in the English classroom was caused by internal factor and external factor. Feeling boredom, feeling anxiety, and seeking attention were internal factor that became the occurrence of disruptive behavior. While fatigue was the external factor that causes the emergence of students' disruptive behavior in the English teaching-learning process in the classroom. Keywords Disruptive Behavior, English Classroom, Senior High School Students, Teachers’ Management